Cellular Levels of Heme Affect the Activity of Dimeric Glutamyl-Trna Reductase - Levican-Jaque, G (2011)
Glutamyl-tRNA reductase (GluTR) is the first enzyme committed to tetrapyrrole biosynthesis by the C5-pathway. This enzyme transforms glutamyl-tRNA into glutamate-1-semi-aldehyde, which is then transformed into 5-amino levulinic acid by the glutamate-1-semi-aldehyde 2,1-aminomutase. Binding of heme to GluTR seems to be relevant to regulate the enzyme function. Recombinant GluTR from Acidithiobacillus ferrooxidans an acidophilic bacterium that participates in bioleaching of minerals was expressed in Escherichia coli and purified as a soluble protein containing type b heme. Upon control of the cellular content of heme in E. coli, GluTR with different levels of bound heme was obtained. An inverse correlation between the activity of the enzyme and the level of bound heme to GluTR suggested a control of the enzyme activity by heme. Heme bound preferentially to dimeric GluTR. An intact dimerization domain was essential for the enzyme to be fully active. We propose that the cellular levels of heme might regulate the activity of GluTR and ultimately its own biosynthesis. © 2011 Elsevier Inc.